THE UNIQUENESS OF PROVERBS IN FOLKLORE - Shokirova Madinabonu Shomurod qizi (International Journal of Innovations in Engineering Research and Technology, 2022)
This article discusses the uniqueness of proverbs in folk art. An opinion is expressed about the difference of proverbs from other types of folk art by being able to express a deep meaning, being concise, mature and thorough.